Density forecasting for tourism demand. (September 2016) - Wan, Shui Ki; Song, Haiyan; Ko, David
Highlights: Introduce usefulness of density forecasts for visitor arrival in risk management. Test the appropriateness of model assumption with histogram-based method. Apply the framework to ARDL model for Hong Kong inbound tourism demand. Error in ARDL model for the demand growth rates of China exhibit fat tail. Normality assumption for the growth rates model from Macau is appropriate.